Using Big Data, An Extensible System for Forecasting and Analyzing Relations Among Crimes (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
While Big Data presents a dilemma for criminal activity analysis, it's even possible to assist them in locating and detecting patterns that can help them crime prevention and investigation. This system intends to draw consideration to current problems in Cyber Crime Investigations – particularly those involving Big Data – as well as potential approaches to combating cybercrime. The proposed system's outcome would help law enforcement and police department agencies a higher comprehension criminal issues and provide insights that will allow them to track operations, forecast the chance of incidents, arrange resources effectively, and optimise policymaking processes. Crime prediction makes use of historical data and, after analysing it, forecasts future crimes based on place and time.Outdated methods become fewer effective as their ability to deliver needed outcomes in an appropriate and supply-constrained manner deteriorates. To prevent and combat crime, one promising choice for Criminal Inquiries is to use tools for computing based on cutting-edge data analytics. As a result, machine learning and computer modelling should be included in the investigations. One of the solutions is computational, which provides quick and effective data analysis to find small sign in big, unstructured data sets.